Development of an Android-based Application as a Solution for Maternal Health - Tarsono; Fachrie, Muhammad (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
This research highlights the problem of lack of accessibility of health services for pregnant women, especially in consultations with doctors and access to pregnancy information. To overcome these challenges, the research aims to develop an application that allows pregnant women to access pregnancy information easily, consult with doctors, and monitor pregnancy progress efficiently. This research proposes the development of an Android-based application as a solution for health care for pregnant women, which uses an approach known as Rapid Application Development (RAD). RAD was chosen because of its reputation as a software development approach with rapid development capabilities and readiness to respond to change. Adopting the RAD method aims to create flexible and responsive applications that can adapt to changes that may occur over time. This learning and consultation application for pregnant women is very helpful for them to always know about their pregnancy. This application is also very useful for health workers. Health workers can quickly help patients at any time. Health workers can also provide advice regarding pregnancy by entering it into the application, which will be very helpful for mothers in maintaining their pregnancy. The research addresses the accessibility of health services for pregnant women. It is hoped that with this application, pregnant women will become more educated and guided about pregnancy so that cases of maternal and infant mortality in Indonesia will decrease.